Research priorities in technical teacher education, a planning model - Miller, Aaron J.; Ohio State Univ., Columbus. Center for Vocational and Technical Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1967)
This research and development model was an outgrowth of a technical education research planning conference of business, industry, government and education representatives to identify some of the critical problems which seem to be impeding the growth of technical education and to suggest research and development priorities for a more unified national research effort toward solutions. Many of the numerous problems identified focused on the area of technical teacher education. As a structure for analyzing the system of technical teacher education, four of its aspects, the role, selection and recruitment, training programs, and evaluation of technical teachers, were examined by identifying questions relevant to problem solutions and reviewing the literature pertinent to the questions. Some research and development activities considered worthy of study were (1) identifying factors related to the career choice of technical teachers, (2) recruiting technical teachers from industry, (3) developing programs to meet potential technical teacher training needs, (4) developing a teaching associate program, (5) analyzing the activities of technical teachers, (6) developing an inservice internship program, (7) forming a cooperative work-experience team, (8) using video tape for inservice training, (9) testing the effectiveness of teacher participation in professional activities, and (10) determining employment criteria for technical education teachers. A bibliography of the literature reviewed and additional references are provided. (hc)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; Educational Problems; Educational Research; Literature Reviews; Models; Program Development; Research Needs; Teacher Education; Teacher Evaluation; Teacher Recruitment; Teacher Role; Teacher Selection; Technical Education; Vocational Education Teachers